The Past Through Narratology New Approaches to Late Antiquity and the Early Middle Ages - Fafinski, Mateusz; Riemenschneider, Jakob (Das Mittelalter. Perspektiven mediävistischer Forschung. Beihefte, 2022)
"The Past through Narratology" proposes a fresh approach to various types of texts from Late Antiquity and the Early Middle Ages. Starting from a broad definition of what a text can be - ranging from hagiographic narratives and maps to archaeological remains - this book proposes narrativity and narratology as frameworks for exploring sources and exchanging opinions. The various contributions in this volume investigate how late antique and early medieval authors and movements used narrative as a vehicle for their ideas and how they operated in literarised spaces. At the same time, this book also examines how we as researchers construct narratives about our periods of study.